Relationship between intellectual capital and financial performance of shariah compliant construction firms / Ahmad Syakir Hamdan and Khasmarina Mohamed Khadzir - Hamdan, Ahmad Syakir; Mohamed Khadzir, Khasmarina (Arshad Ayub Graduate Business School, 2018)
Intellectual Capital has been used in past few studies to analyse its’ relationship on firms’ performance. As intangible resources, the researchers and also financial management organizations intend to know how these resources can create value to the firms and can improve the firms’ financial performance. This intangible resource also been in Malaysia Plan since 8th Malaysia Plan until to date 11th Malaysia Plan and has been main agenda to boost the growth of the Malaysia’s economy. Construction sector is one of the main contributor to the growth of Malaysia economy reported in the past Malaysia Plan’s achievement in terms of good compounded annual growth rates. This study will focus on construction firms which Shariah compliant and listed in Bursa Malaysia because of none studies previously carried-out on Shariah compliant firms and the sector also is the most highest Shariah compliant contributions out of its’ sector total securities listed in Bursa Malaysia. This paper will focus on exploring the components of Intellectual Capital (human capital efficiency, structural capital efficiency and capital employed efficiency) and its’ influence on the performance of Shariah compliant construction firms listed in Bursa Malaysia. The findings have indicated that capital employed efficiency is the component that have significantly influenced on the performance of Shariah compliant construction firms listed in Bursa Malaysia. The results of this research have created important implications for investors, managers as well as policy makers in order for them to make strategic investments and financial decisions. This research also helps to fill the gaps exist in this research area when conducting research on components of intellectual capital that influence the Shariah compliant construction firms listed in Bursa Malaysia.